Features of epithelial-mesenchymal transition in ectopic endometrium in patients with extragenital endometriosis of various localizations. Observational study - Eugeniu Cazacu; Eremei Zota; Mariam A. Vardanyan; Radu Niguleanu; Ruslan Pretula; Aleksandra V. Asaturova; Larisa S. Ezhova; Alina S. Badlaeva (IP Berlin A.V., 2024)
Background. Epithelial-mesenchymal transition (EMT) is a conserved mechanism in the process of morphogenesis and organogenesis. EMT provides cells with migratory and invasive properties, which is a necessary condition for the formation of endometrioid heterotopias. Aim. To confirm the presence of EMT features in different types of endometriosis. Materials and methods. During a period of five years (2012-2017) we analyzed 43 cases of extragenital endometriosis: appendix (3 case), colon (5 cases), ileum (1 case), abdominal scar endometriosis after caesarean section (24 cases), and inguinal hernia (10 cases). The material was processed according to histological and immunohistochemical technique using monoclonal E-cadherin and polyclonal Vimentin antibodies to assess local invasiveness. Results. In peritoneal endometriosis, the ratio of E-cadherin to Vimentin expression was 10.3, in the colon = 9.1, in the appendix 8.6, in the ileum 5.5, in the hernial sac 4.2. Thus, in diffuse infiltrative forms of endometriosis, the lesion phenotype is characterized by low expression of E-cadherin, while expression of Vimentin is at a high level (p0.05). Conclusion. The results of our study confirmed involvement of the epithelial-mesenchymal transition process in the pathogenesis of extragenital endometriosis lesions, on the one hand, and they certify its invasive potential in these localizations, on the other hand.